2020
DOI: 10.3390/molecules25051117
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Auraptene Induces Expression of Brain-Derived Neurotrophic Factor in Neuro2a Cells

Abstract: (1) Background: Our published data have indicated that (1) auraptene (AUR), a citrus ingredient, has neuroprotective effects on the mouse brain, owing to its ability to suppress inflammation, such as causing a reduction in hyperactivation of microglia and astrocytes; (2) AUR has the ability to trigger phosphorylation (activation) of extracellular signal-related kinase (ERK) and cAMP response element-binding protein (CREB) in neuronal cells; (3) AUR has the ability to induce glial cell line-derived neurotrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…53) GDNF, which was originally found as a trophic agent for midbrain dopamine neurons, has pronounced neuroprotective effects in various nervous system pathologies, including ischemic brain damage and neurodegenerative diseases. 54) AUR also slightly but significantly induced bdnf gene expression via the upregulated ERK/CREB pathway in neuro2a cells. 55) Those in vitro study results suggested that the induction of neurotrophic factor in astrocytes and neurons may be one of the mechanisms partially accounting for the neuroprotective effects of AUR.…”
Section: Neuroprotective Effects Of Aur In the Brainmentioning
confidence: 89%
See 1 more Smart Citation
“…53) GDNF, which was originally found as a trophic agent for midbrain dopamine neurons, has pronounced neuroprotective effects in various nervous system pathologies, including ischemic brain damage and neurodegenerative diseases. 54) AUR also slightly but significantly induced bdnf gene expression via the upregulated ERK/CREB pathway in neuro2a cells. 55) Those in vitro study results suggested that the induction of neurotrophic factor in astrocytes and neurons may be one of the mechanisms partially accounting for the neuroprotective effects of AUR.…”
Section: Neuroprotective Effects Of Aur In the Brainmentioning
confidence: 89%
“…54) AUR also slightly but significantly induced bdnf gene expression via the upregulated ERK/CREB pathway in neuro2a cells. 55) Those in vitro study results suggested that the induction of neurotrophic factor in astrocytes and neurons may be one of the mechanisms partially accounting for the neuroprotective effects of AUR.…”
Section: Neuroprotective Effects Of Aur In the Brainmentioning
confidence: 89%
“…The same pattern was observed for the expression of GDNF mRNA. As a continuation of their studies, Furukawa et al (2020) determined also that auraptene had a deep effect on the release and expression of the brain-derived neurotrophic factor (BDNF) in mouse neuroblastoma 2a cells (Furukawa et al 2020).…”
Section: Auraptenementioning
confidence: 97%
“…e induction of the brain-derived neurotrophic factor (BDNF) in neuronal cells was suggested to be one of the mechanisms accounting for the neuroprotective effects exerted by AUR. e BDNF mRNA levels and secreted BDNF in neuro-2a cells were significantly increased by AUR in a dose-and time-dependent manner [132].…”
Section: Citrus Fruit (Citrus Spp)mentioning
confidence: 97%
“…7-[(2E)-3,7-Dimethylocta-2,6-dienoxy]chromen-2-one (auraptene) is a coumarin derivative, which has been reported to possess various pharmacological properties including neuroprotective effects [131] on the mouse brain by suppressing inflammation, e.g., through reduction in hyperactivation of microglia and astrocytes [132]. e antiinflammatory effects were not only on the peripheral organs but also the brain of a mouse model of global cerebral ischemia [133,134] and lipopolysaccharide-(LPS-) induced systemic inflammation [135,136].…”
Section: Citrus Fruit (Citrus Spp)mentioning
confidence: 99%